Proposed interior design of Warisan Restaurant at Lot 23,23A & 23B Jalan Plumbum P7/P, 40000 Shah Alam Selangor Darul Ehsan for Warisan Restaurant / Nurain Nabila Masri - Masri, Nurain Nabila (Faculty of Architecture, Planning and Surveying, 2012)
As for years, discerning visitors in search of casual dining in Kuala Lumpur hand one word at the top the list warisan. Now, following a major re-modelling. Warisan restaurant will soon open its doors to an even more sumptuous and memorable experience, and a very warm welcome awaits customers old and new. From the moment you arrive and escorted to your table you’ll see the lifestyle’s of Malaysian in the restaurant. The chef has created an exciting Malaysian foods inspired menu to please the most demanding taste. Special events such as weddings, birthdays, corporate entertaining can also be catered for in the main restaurant or the new private dining area. The restaurant has an outdated concept and this is the main factor why the customers are not interested to come to th restaurant.This issue will be solved by designer after analyzing all the data and details for design process.The aim of this project is to create a new design and environment for an restaumant in order to achieve a satisfied to a customers.